2015
DOI: 10.3109/09513590.2015.1062865
|View full text |Cite
|
Sign up to set email alerts
|

Classic PCOS phenotype is not associated with deficiency of endogenous vitamin D and VDR gene polymorphisms rs731236 (TaqI), rs7975232 (ApaI), rs1544410 (BsmI), rs10735810 (FokI): a case–control study of lower Silesian women

Abstract: For the first time, we show that endogenous vitamin D deficiency and VDR polymorphisms are not associated with homogeneous "classic" PCOS phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…It is worth noting that all the VDR genotypes were related to declined NSCLC risk. An increased risk comparing TT vs. CC in Taq1 in our study is consistent with the results observed in previous studies [50,51,52]. On the other hand, there are a few other studies that have also found no association with increased risk [53,54].…”
Section: Discussionsupporting
confidence: 93%
“…It is worth noting that all the VDR genotypes were related to declined NSCLC risk. An increased risk comparing TT vs. CC in Taq1 in our study is consistent with the results observed in previous studies [50,51,52]. On the other hand, there are a few other studies that have also found no association with increased risk [53,54].…”
Section: Discussionsupporting
confidence: 93%
“…) and changes in this protein quantity could affect the insulin secretor capacity . Therefore, several studies relating these polymorphisms with the PCOS phenotype have been conducted (Tables ) …”
Section: Vitamin D Receptor Polymorphisms In Pcosmentioning
confidence: 99%
“…Jedrzejuk et al . coordinated the most recent study . FokI, BsmI, ApaI, and TaqI polymorphisms were analyzed in a lower Silesian population, aged 20–35 years, who were divided into two groups: classic PCOS ( n = 92) and healthy ( n = 85).…”
Section: Vitamin D Receptor Polymorphisms In Pcosmentioning
confidence: 99%
See 2 more Smart Citations